Intersecting identities: investigating effects of multiple hierarchy stratification perspective on visitor activity participation - Wilkes, Jessica A. (Kansas State University, 2023)
This study uses a multiple hierarchical stratification perspective to investigate the probability of activity participation among 1,774 Joshua Tree National Park visitors who responded to a visitor survey in 2019. According to the multiple hierarchy stratification perspective, an individual’s demographic characteristics interact and affect their social position and therefore their access to services or resources. The purpose of the study is to gain a deeper understanding of how the combination of visitors’ demographic characteristics affects the probability of activity participation in a U.S. National Park. Binary logistic regression models were employed to determine how the multiplicative effects of four status characteristics, age, gender, race/ethnicity, and education, impact the probability of visitors’ participation in 20 various activities. Additionally, the high diversity of California is accounted for with the inclusion of California residency as a moderating variable. The results indicate differences in the probability of participation in specific activities like camping, rock scrambling, technical climbing, and picnicking as well as significant effects of residing in California on specific activities. Overall, there were few clear linear trends present for the models, but the results provide validity to the use of a data analysis tool that can be employed to identify activity participation trends with an intersectional approach at a popular U.S. National Park. The methods can be incorporated into existing monitoring procedures using demographic data routinely collected by public land managers and organizations that support public lands and/or visitors.
Keywords: Visitor activity participation; Multiple hierarchy stratification perspective; Intersectionality; U.S. national park; California; Visitor use management